2009
DOI: 10.1021/cm901163t
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional-Hexagonal Periodic Mesoporous Polymer Resin Thin Films by Soft Templating

Abstract: Two-dimensional (2D)-hexagonal (plane group, p6mm) mesoporous polymer resin thin films were obtained through evaporation-induced organic-organic self-assembly of a preformed oligomeric resol precursor and the triblock copolymer template pluronic P123. The polymer resin films were prepared on silicon wafers by spin-coating a mixture of precursor and surfactant in ethanol. Evaporation-induced self-assembly is followed by the formation of a condensed-wall material through thermopolymerization of the precursor oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 27 publications
5
48
1
Order By: Relevance
“…This is related to a restricted shrinkage behavior in contrast to thin films, in which uniaxial shrinkage of around 50 % occurs. [15] From 400 to 600 8C ( Figure 1C), only small peak shifts to higher angles are visible, whereas no further shrinkage to 1000 8C can be observed. Even at 1000 8C ( Figure 1D), the SAXS pattern shows intense peaks and higher-order reflections.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is related to a restricted shrinkage behavior in contrast to thin films, in which uniaxial shrinkage of around 50 % occurs. [15] From 400 to 600 8C ( Figure 1C), only small peak shifts to higher angles are visible, whereas no further shrinkage to 1000 8C can be observed. Even at 1000 8C ( Figure 1D), the SAXS pattern shows intense peaks and higher-order reflections.…”
Section: Resultsmentioning
confidence: 95%
“…Further progress concerning high thermal stability or easier synthesis conditions for bulk materials was achieved by Wang et al [13] and Lu et al [14] A soft-templating pathway that led to thin films with face-centered orthorhombic (Fmmm) symmetry was reported by Tanaka et al [9] Recently we reported a soft-templating method for highly ordered mesoporous polymer resin thin films with a 2D-hexagonal order (P6mm). [15] Mesoporous phases within the pores of anodic alumina membranes (AAM) were first achieved with mesoporous silica. In 2003, Yang et al [16] synthesized a circular hexagonal mesoporous silica phase, in which the mesopores form circles around the axis of the columnar AAM pores (or the membrane normal).…”
Section: Introductionmentioning
confidence: 99%
“…The film thickness is around 200 nm after thermopolymerization for all samples. 14 The incident angle of the GISAXS setup was relatively high (0.3°) as compared to Bang et al, 40 thus the X-rays should penetrate the full film thickness. Doubling of reflections in z-direction arises from diffraction of the reflected incident beam.…”
Section: ■ Characterizationmentioning
confidence: 90%
“…The resulting material was black, consistent with the expected carbon residue. 28,69,71,72,101,102 This compression complicates SAXS analysis since the orientation of the powdered sample was unknown and thus the longest real-space d 10 dimension from the elliptical scattering pattern was assumed to coincide with the lm normal and was thus used for comparison. S2a †).…”
Section: Mesoporous Materialsmentioning
confidence: 99%